2017
DOI: 10.1039/c7cp03376a
|View full text |Cite
|
Sign up to set email alerts
|

Radical-driven processes within a peptidic sequence of type I collagen upon single-photon ionisation in the gas phase

Abstract: We report on an experimental single-photon absorption study on gas-phase protonated collagen peptides employing a combination of mass spectrometry and synchrotron radiation. Partial ion yields for the main photoabsorption products vary steadily with photon energy over the range from 14 to 545 eV. At low energy, non-dissociative photoionisation competes with neutral molecule loss from the precursor ion, whereas fragmentation of the peptide backbone dominates at soft X-ray energies. Neutral molecule losses from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 56 publications
6
25
0
Order By: Relevance
“…Figure ), we observe an increase of [V−H−CO 2 ] − and [R−H−CO 2 ] − . In this energy range, we have previously demonstrated that the amount of transferred vibrational energy increases, it is therefore in line with our hypothesis of [V−H−CO 2 ] − and [R−H−CO 2 ] − being due to internal conversion and intramolecular vibrational energy redistribution after electron detachment.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Figure ), we observe an increase of [V−H−CO 2 ] − and [R−H−CO 2 ] − . In this energy range, we have previously demonstrated that the amount of transferred vibrational energy increases, it is therefore in line with our hypothesis of [V−H−CO 2 ] − and [R−H−CO 2 ] − being due to internal conversion and intramolecular vibrational energy redistribution after electron detachment.…”
Section: Resultssupporting
confidence: 92%
“…It is insightful to compare our results on complexes of vancomycin and Ac 2 L K D A D A receptor mimic to those obtained by Roepstorff and co‐workers: they have shown that CID at 70 eV kinetic energy in the laboratory frame leads to the same fragmentation yield for doubly deprotonated as for doubly protonated complexes. The fact that our results indicate that VUV photoabsorption induces less fragmentation for the doubly deprotonated complex might come from the radical species created after electron removal: radical‐mediated processes have been shown to play an important role, both for protonated and deprotonated peptides for instance . In low‐energy CID, these processes are negligible for closed‐shell species and instead, charge‐remote or charge‐directed mechanisms are dominant .…”
Section: Resultsmentioning
confidence: 65%
“…Moreover, we do not observe such an intense peak corresponding to H 2 O loss from the precursor. This is consistent with this process being due to ionization and occurring with a very low barrier, presumably a radical-driven rearrangement followed by H 2 O loss, akin to the case of the 423-448 sequence of collagen 22 . where and are the absolute integrated area under the peak(s) of interest and the precursor ion depletion peak, respectively.…”
Section: Non-dissociative Ionization Of Peptide Monomerssupporting
confidence: 65%
“…This loss is observed from doubly and triply protonated (PHypG) 10 and to a much weaker extent from (PPG) 10 (see figure S2). We have already observed similarly pronounced H 2 O loss for a collagen hydroxylated peptide (the 423-448 amino-acid sequence of the α-1 chain of type I collagen), together with loss of other neutral molecules, and showed that they originate from sidechains 22 . Contrary to proline, the hydroxyproline side-chain contains an OH group, which is most probably involved in the pronounced H 2 O loss.…”
Section: Non-dissociative Ionization Of Peptide Monomersmentioning
confidence: 91%
“…Depending on the protein size, soft X‐ray photoionization can lead to small fragments (often immonium ions), sequence ions, as well as intact ionized proteins or ionized proteins that have lost neutral groups 15. For melittin at room temperature, these channels are known to coexist 16.…”
mentioning
confidence: 99%